Using the Model View Controller (MVC) Method in Medicament Sales Information System Design - Nur Hidayati (Jurnal Riset Informatika, 2020)
Sales have an important role in an organization, especially medicament sales at Pharmacies, especially at Apotik Bubulak Bogor. The use of a good information system is certainly very necessary for the Pharmacy to manage its data. In managing its sales data, this Pharmacy still uses a conventional system, so various problems arise, such as miscalculations in making reports, often forgetting to record transactions that occur, and many still use paper as a documentation tool. So, it is necessary to design a system to be implemented in the sales system. To be able to overcome various existing problems, the new system can be more effective, and the data produced more accurately. Therefore, to achieve this goal, it is necessary to use the right method, namely the MVC (Model View Controller) method. This MVC method can show the needs needed in building the information system. A good result of this MVC method is to separate the application logic process from the user interface.